2021
DOI: 10.1093/jamia/ocab196
|View full text |Cite|
|
Sign up to set email alerts
|

Gender harmony: improved standards to support affirmative care of gender-marginalized people through inclusive gender and sex representation

Abstract: Objective Accurate representation of clinical sex and gender identity in interoperable clinical systems is a major challenge for organizations intent on improving outcomes for sex- and gender-marginalized people. Improved data collection has been hindered by the historical approach that presumed a single, often binary, datum was sufficient. We describe the Health Level Seven International (HL7) Gender Harmony logical model that proposes an improved approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The data collection instrument was created to reflect GSSO variables identified as ideal documentation and data elements by GSSO researchers, health systems, expert consensus work, and technical standards development organizations. [23][24][25][26]31,35 The data collection instrument was designed to allow for the examination of conceptual coverage for inclusive digital representation of GSSO clinical variables, planning, and interventions. Given the progressive evolution of scientific and social perspectives on some of the GSSO terms, definitions, and clinical impacts, more contemporary initiatives and publications (prior to 2018) were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection instrument was created to reflect GSSO variables identified as ideal documentation and data elements by GSSO researchers, health systems, expert consensus work, and technical standards development organizations. [23][24][25][26]31,35 The data collection instrument was designed to allow for the examination of conceptual coverage for inclusive digital representation of GSSO clinical variables, planning, and interventions. Given the progressive evolution of scientific and social perspectives on some of the GSSO terms, definitions, and clinical impacts, more contemporary initiatives and publications (prior to 2018) were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The only preliminary information needed to appropriately interact with a patient is gained by asking for their affirmed name and pronouns. If the clinic or program currently produces or plans to engage in research generated from medical records, gathering information pertaining to sex and gender as part of a patient’s chart may be important, especially if seeking to contribute to research geared toward improving health care and/or health outcomes for people who experience marginalization based on gender (Bauer et al 2017; McClure et al 2022). While beyond the scope of this article, special consideration should be given to how this information is obtained and recorded for research purposes, including ensuring a clear distinction between sex assigned at birth and gender identity (McClure et al 2022).…”
Section: Paperworkmentioning
confidence: 99%
“…Studies reported that most existing applications do not adopt standards including gender identity, assigned gender at birth, or gender markers on health insurance documents, and that they do not consider diversity in gender, sex, and sexual orientation (GSSO) data [73,74]. Work by Kronk et al [20], McClure et al [75], and Davison et al [76] has surveyed the current landscape of GSSO data in EHRs and provided newer frameworks to reassess data collection standards. Recommendations in this work included an overhaul to the existing Health Level 7 (HL7) sex and gender model, as well as implementation of a two-step process (of gender identity and assigned gender at birth [AGAB]) in clinical contexts.…”
Section: Replicating (In)equity In Designmentioning
confidence: 99%